Dual checkpoint targeting of B7-H3 and PD-1 with enoblituzumab and pembrolizumab in advanced solid tumors: interim results from a multicenter phase I/II trial. Issue 4 (12th April 2022) - Aggarwal, Charu; Prawira, Amy; Antonia, Scott; Rahma, Osama; Tolcher, Anthony; Cohen, Roger B; Lou, Yanyan; Hauke, Ralph; Vogelzang, Nicholas; P Zandberg, Dan; Kalebasty, Arash Rezazadeh; Atkinson, Victoria; et al.
Abstract : Background: Availability of checkpoint inhibitors has created a paradigm shift in the management of patients with solid tumors. Despite this, most patients do not respond to immunotherapy, and there is considerable interest in developing combination therapies to improve response rates and outcomes. B7-H3 (CD276) is a member of the B7 family of cell surface molecules and provides an alternative immune checkpoint molecule to therapeutically target alone or in combination with programmed cell death-1 (PD-1)–targeted therapies. Enoblituzumab, an investigational anti-B7-H3 humanized monoclonal antibody, incorporates an immunoglobulin G1 fragment crystallizable (Fc) domain that enhances Fcγ receptor-mediated antibody-dependent cellular cytotoxicity. Coordinated engagement of innate and adaptive immunity by targeting distinct members of the B7 family (B7-H3 and PD-1) is hypothesized to provide greater antitumor activity than either agent alone. Methods: In this phase I/II study, patients received intravenous enoblituzumab (3–15 mg/kg) weekly plus intravenous pembrolizumab (2 mg/kg) every 3 weeks during dose-escalation and cohort expansion. Expansion cohorts included non–small cell lung cancer (NSCLC; checkpoint inhibitor [CPI]–naïve and post-CPI, programmed death-ligand 1 [PD-L1] <1%), head and neck squamous cell carcinoma (HNSCC; CPI-naïve), urothelial cancer (post-CPI), and melanoma (post-CPI). Disease was assessed using Response Evaluation Criteria in Solid Tumors version 1.1 after 6 weeks and every 9 weeks thereafter. Safety and pharmacokinetic data were provided for all enrolled patients; efficacy data focused on HNSCC and NSCLC cohorts. Results: Overall, 133 patients were enrolled and received ≥1 dose of study treatment. The maximum tolerated dose of enoblituzumab with pembrolizumab at 2 mg/kg was not reached. Intravenous enoblituzumab (15 mg/kg) every 3 weeks plus pembrolizumab (2 mg/kg) every 3 weeks was recommended for phase II evaluation. Treatment-related adverse events occurred in 116 patients (87.2%) and were grade ≥3 in 28.6%. One treatment-related death occurred (pneumonitis). Objective responses occurred in 6 of 18 (33.3% [95% CI 13.3 to 59.0]) patients with CPI-naïve HNSCC and in 5 of 14 (35.7% [95% CI 12.8 to 64.9]) patients with CPI-naïve NSCLC. Conclusions: Checkpoint targeting with enoblituzumab and pembrolizumab demonstrated acceptable safety and antitumor activity in patients with CPI-naïve HNSCC and NSCLC. Trial registration number: NCT02475213 .